THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE TROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT CONVENTIONAL STATE-OWNED BANKS IN THE BEKASI AREA - Agrasadya, Agrasadya; Notosudjono, Didik; Yusnita, Nancy (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to the influence of organizational culture on employee performance through job satisfaction as an intervening variable. This study was conducted using a quantitative approach. Organizational culture has a significant positive effect on performance, which can be interpreted that the organizational culture variable has a positive effect on the performance variable or it can be said that the higher the organizational culture, the higher the performance, conversely the lower the organizational culture, the lower the performance. Job satisfaction has a significant positive effect on performance, which can be interpreted that the job satisfaction variable has a positive effect on the performance variable or it can be said that the higher the job satisfaction, the higher the performance, conversely the lower the job satisfaction, the lower the performance. Organizational culture has a significant positive effect on job satisfaction, which can be interpreted that the organizational culture variable has a positive effect on the job satisfaction variable or it can be said that the higher the organizational culture, the higher the job satisfaction, conversely the lower the organizational culture, the lower the job satisfaction. Organizational culture has a significant effect on performance which is positively mediated by job satisfaction.